Recovery of the X-ray polarisation of Swift J1727.8-1613 after the soft-to-hard spectral transition - Podgorny, J.; Svoboda, J.; Dovciak, M.; Veledina, A.; Poutanen, J.; Kaaret, P.; Bianchi, S.; Ingram, A.; Capitanio, F.; Datta, S. R.; Egron, E.; Krawczynski, H.; et al. (EDP SCIENCES S A, 2025)
We report on the detection of X-ray polarisation in the black-hole X-ray binary Swift J1727.8-1613 during its dim hard spectral state by the Imaging X-ray Polarimetry Explorer (IXPE). This is the first detection of X-ray polarisation at the transition from the soft to the hard state in an X-ray binary. We find an averaged 2-8 keV polarisation degree of (3.3 +/- 0.4)% and a corresponding polarisation angle of 3 degrees +/- 4 degrees, which matches the polarisation detected during the rising stage of the outburst, in September-October 2023, within 1 sigma uncertainty. The observational campaign complements previous studies of this source and enables comparison of the X-ray polarisation properties of a single transient across the X-ray hardness-intensity diagram. The complete recovery of the X-ray polarisation properties, including the energy dependence, came after a dramatic drop in the X-ray polarisation during the soft state. The new IXPE observations in the dim hard state at the reverse transition indicate that the accretion properties, including the geometry of the corona, appear to be strikingly similar to the bright hard state during the outburst rise despite the X-ray luminosities differing by two orders of magnitude.